Impact of A Learning Approach Based on Feedback (Immediate and Delayed) on Learning Chest Passing Skill in Basketball for Students - Ramy Jabbar Kazem Abboud (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
Despite extensive assertions by curriculum, teaching methodologies, and movement science experts regarding crucial role of feedback as a pivotal variable in improving educational outcomes and acquiring motor skills, field observations and the researcher's practical experience in educational institutions, particularly in context of working with individuals with various special needs, revealed shortcomings in optimal scientific and technical application of feedback strategies by teaching staff. The researcher adopted experimental method, as it is the most suitable approach for verifying cause-and-effect relationships between independent and dependent variables. Experimental design, based on two equivalent groups, was implemented includes pre- and post-test, to ensure isolation of extraneous variables and to verify true effect of feedback patterns (immediate and delayed) on learning the skill under study. Sample was defined as the fifth-grade students at Al-Mudhariyah Primary School for Boys during 2023-2024 academic year, totaling (90) students with an average age of (11) years, sample was selected using simple random sampling, comprising (30) students, representing approximately 34% of the original community. Current research aims to check effectiveness of immediate feedback and late  In developing the technical performance skill of chest passing in basketball, to reveal effectiveness of both feedback (immediate and delayed) and extent of their impact on acquiring and mastering basketball rebounding skill. Results show real-time feedback has proven to be tangibly effective in accelerating acquisition of chest passing skills among students, statistically significant differences in favor of this type of information provision. Results revealed no statistically significant differences between two feedback patterns (immediate and delayed) in pre-test stage, confirming homogeneity of research groups and randomness of initial differences before intervention of independent variable.